1989
DOI: 10.1093/geront/29.4.457
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Alternative Support Strategies on Family Caregiving

Abstract: Family units (N = 541) of impaired elderly persons and caregivers were randomly assigned to a control group or one of five treatment groups eligible for a variety of respite or educational services. After 12 months of service eligibility, caregivers of elderly persons remaining in the community reported lower levels of subjective burden. Services appeared to delay nursing home placement among families with adult child caregivers, but encouraged placement by spouse caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
120
2
6

Year Published

1993
1993
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(134 citation statements)
references
References 0 publications
6
120
2
6
Order By: Relevance
“…Batswana caregivers expressed a need to be able to meet basic survival needs, such as food, sanitation, soap and shelter. In contrast, the Western literature focusses on the need for flexible work schedules, psychological counselling, respite care and the provision o f supportive assistance (Biegel & Blum, 1990;Crossman, London & Barry, 1981;Hooyman, 1992;Montgomery & Borgatta, 1989;Montgom ery & Prothero, 1986). Such needs were not even considered by caregivers in Botswana, who are still struggling with basic physical, material and survival needs.…”
Section: Discussionmentioning
confidence: 99%
“…Batswana caregivers expressed a need to be able to meet basic survival needs, such as food, sanitation, soap and shelter. In contrast, the Western literature focusses on the need for flexible work schedules, psychological counselling, respite care and the provision o f supportive assistance (Biegel & Blum, 1990;Crossman, London & Barry, 1981;Hooyman, 1992;Montgomery & Borgatta, 1989;Montgom ery & Prothero, 1986). Such needs were not even considered by caregivers in Botswana, who are still struggling with basic physical, material and survival needs.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, this distinction obeys the specific development of the burden concept and points to the multidimensionality of the impact of care (Montgomery and Borgatta, 1989). Thus, in the first moment, the burden term was elaborated as a subjective perception of the impact of care by the caregiver, where subjective burden refers to the attitudes and emotional reaction of the caregiver faced with the development of the care, such as for example, a low emotional mood, anxiety, or depression.…”
Section: The Burden Concept: Theoretical Perspectives About Caregivermentioning
confidence: 99%
“…has been expressed by spouses of stroke patients (Denman, 1998 Caregiver reactions to offers of respite care may depend to some extent on the nature of the relationship between the informal carer and the dependent person (Clarke and Watson, 1991). However, resphe services may enable continumg employment for the caregiver or simply aUow the caregiver to have a break from their caregiving responsibiUties, Some studies have highlighted the psychological benefits of respite care for famUy caregivers (Zarit et al, 1998) yet others have suggested that resphe care has Uttle impact on caregiver mental health and has not been found to delay nursing home placement (Lawton et al, 1991;Montgomety and Borgatta, 1989). Moreover, a systematic review of respite intervention studies revealed 29 studies from which there was Uttle evidence that resphe intervention has either a consistent or enduring beneficial effect on carers' weU-being (McNaUy et al, 1999).…”
Section: Respite Carementioning
confidence: 99%